2020
DOI: 10.3390/pathogens9030212
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Nucleotide Diversity of Yr15 in Wild Emmer Populations and Chinese Wheat Germplasm

Abstract: Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a devastating fungal disease of wheat. The wild emmer gene, Yr15 (Wtk1), which confers a strong broad-spectrum resistance to Pst isolates, is composed of kinase and pseudokinase domains. The analysis of 361 wild emmer accessions from a wide range of natural habitats confirms that functional Wtk1 is distributed mainly along a narrow axis from Mt. Carmel to Mt. Hermon regions, in the northern part of Israel, where environmental conditions are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…To date, many wheat stripe rust resistance genes have been identi ed, some of which were derived from the progenitors or wild relatives of wheat, including Yr5, Yr8, Yr9, Yr15, Yr17, Yr19, Yr28, Yr35, Yr36, Yr37, Yr38, Yr40, Yr42, Yr50, Yr69, Yr70, Yr83, and Yr84 (Gong et al 2022;Klymiuk et al 2022;Li et al 2020). Some of these resistance genes have been widely used by wheat breeders (e.g., Yr5, Yr9, Yr15, Yr17, Yr24, Yr28, and Yr36) (Bariana and Mcintosh 1994;He et al 2020;Zhou et al 2017). Among the 348 wheat germplasm resources analyzed by Dong et al (2019) for the presence of stripe rust resistance genes, 122 were revealed to carry Yr5.…”
Section: Utility Of Yr4el For Wheat Breeding To Enhance Stripe Rust R...mentioning
confidence: 99%
“…To date, many wheat stripe rust resistance genes have been identi ed, some of which were derived from the progenitors or wild relatives of wheat, including Yr5, Yr8, Yr9, Yr15, Yr17, Yr19, Yr28, Yr35, Yr36, Yr37, Yr38, Yr40, Yr42, Yr50, Yr69, Yr70, Yr83, and Yr84 (Gong et al 2022;Klymiuk et al 2022;Li et al 2020). Some of these resistance genes have been widely used by wheat breeders (e.g., Yr5, Yr9, Yr15, Yr17, Yr24, Yr28, and Yr36) (Bariana and Mcintosh 1994;He et al 2020;Zhou et al 2017). Among the 348 wheat germplasm resources analyzed by Dong et al (2019) for the presence of stripe rust resistance genes, 122 were revealed to carry Yr5.…”
Section: Utility Of Yr4el For Wheat Breeding To Enhance Stripe Rust R...mentioning
confidence: 99%
“…The highly virulent Pst race CYR34 (virulent on Yr1, Yr6, Yr7, Yr8, Yr9, Yr10, Yr17, Yr18, Yr24, Yr26, Yr27, Yr28, Yr29, Yr31, Yr43, Yr44, YrExp2, and YrSP) (Wang et al 2019b) was used to inoculate the plants at the second leaf stage. Urediniospores used for inoculation of leaf tissue were rst suspended in isododecane and then sprayed as described previously (He et al 2020). Disease severity was evaluated and characterized 14-21 days after inoculation using a 0-9 scale of infection type (IT) (Line and Qayoum 1992).…”
Section: Stripe Rust Resistance Responsementioning
confidence: 99%